2018
DOI: 10.3390/insects9040128
|View full text |Cite
|
Sign up to set email alerts
|

Application of Trap Cropping as Companion Plants for the Management of Agricultural Pests: A Review

Abstract: Companion planting is a well-known strategy to manage insect pests and support a natural enemy population through vegetative diversification. Trap cropping is one such type of special companion planting strategy that is traditionally used for insect pest management through vegetative diversification used to attract insect pests away from the main crops during a critical time period by providing them an alternative preferred choice. Trap crops not only attract the insects for feeding and oviposition, but also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 109 publications
0
33
0
Order By: Relevance
“…The deliberate use of weed species to attract natural enemies for insect pests' population regulation has been studied extensively (Sarkar et al 2018). The findings here suggest that this approach to pest management (when Considering that the identified taxa were assigned up to the genus level, it is quite hard to anticipate the origin of those taxa in the samples analysed.…”
Section: Resultsmentioning
confidence: 87%
“…The deliberate use of weed species to attract natural enemies for insect pests' population regulation has been studied extensively (Sarkar et al 2018). The findings here suggest that this approach to pest management (when Considering that the identified taxa were assigned up to the genus level, it is quite hard to anticipate the origin of those taxa in the samples analysed.…”
Section: Resultsmentioning
confidence: 87%
“…earlier flowering, preferred flower colour or scent have been used as the basis of various trap cropping strategies (reviewed by, e.g. Hokkanen 1991;Parolin et al 2012;Sarkar et al 2018). Dead-end trap crops have the benefit of fast and cost-effective reduction of pest populations (e.g.…”
Section: Svoc-producing Secondary Plants In Sustainable Crop Productimentioning
confidence: 99%
“…Recently, Mukoye and collaborators [55] reported yield losses ranging from 10-100% in Western Kenya. The use of clean seeds and resistant varieties are the most cost-effective practices to control viruses [55], but recent research has shown promising results with IPM and the use of plant extracts in controlling the transmission agents, i.e., pests [56]. The use of allelopathic effects, a technology that has gained prominent use to manage field pests in Asia and Latin America [57][58][59] is also another alternative to be explored in Africa.…”
Section: Biotic Stress: Pests Diseases and Weedsmentioning
confidence: 99%
“…The use of allelopathic effects, a technology that has gained prominent use to manage field pests in Asia and Latin America [57][58][59] is also another alternative to be explored in Africa. Trap cropping [56], a well-known strategy to manage insect pest through diversification of the plant strata to stimulate the population of natural enemies is also a practice to be massified.…”
Section: Biotic Stress: Pests Diseases and Weedsmentioning
confidence: 99%